Synthesis of 2[N-Cinnamlideneamino]-5-Nitro Phenol and Its Metal(II) Complexes and Evaluation of Their Antitumor Activities - FAWZY EL-HUSSEINY, AMEL (Asian Journal of Chemistry, 2009)
The preparation of a series of metal(II) complexes (Zn, Cu, Co andNi) with 2[N-(cinnamlidene)amino]-5-nitro phenol as a novel ligandand their biological evaluation against six species of pathogenic yeasts(Candida albicans, C. fructus, C. glabrata, C. oleophila, C. parapsilosisand C. tropicalis) are described. All new compounds were fully characterizedby elemental analyses, spectroscopic measurements (IR, UV-vis,NMR, ESR and EIMS) as well as thermal and magnetic susceptibilitymeasurements. Studies revealed that HL ligand acts as bidentate throughN and O atoms. Zn(II) and Co(II) complexes exhibited tetrahedralgeometry while Cu(II), Ni(II) are octahedral. Both Co(II) and Zn(II)complexes exhibited potential antitumor activities and the latter showedpromising cytotoxicity (70-82 % cell mortality) and it may be considereda new antitumor agents.